Dendrochronology and radiocarbon dating of subfossil conifer logs from a peat bog, Maramureş Mts, Romania. (10th September 2016) - Árvai, Mátyás; Popa, Ionel; Mîndrescu, Marcel; Nagy, Balázs; Kern, Zoltán
Abstract: Fifty-six subfossil samples, dominantly Norway spruce ( Picea abies (L.) Karst.), have been collected between 2010 and 2014 from a peat bog located on the Vinderel Plateau, Farcău Massif, Maramureş Mountains (Romania). Seven floating chronologies have been developed. The longest floating chronology contains 259 years while the shortest one spans 56 years. The oldest and youngest ages obtained from six of the radiocarbon dated samples are 1717 ± 19 14 C BP (255–388 cal AD) and 1039 ± 16 14 C BP (985–1023 cal AD), respectively. The floating chronologies provide incomplete coverage of the c. 200 to 1326 AD period. These floating chronologies, supported with 14 C dates, provide a crucial step towards the production of an Eastern Carpathians composite coniferous chronology. The lack of trunk accumulation after the early-14th century suggests the disappearance of trees from the proximity of the site. It closely follows the sharp increase of grazing indicator pollens in the region around the late-13th century. Conjunctly, this evidence points to a substantial landscape/land use change from forest to pasture during the 13th century which probably indicates the beginning of the typical traditional vertical transhumance which became a characteristic livestock management in the Maramureş region over the past centuries.